Pengaruh Kompensasi terhadap Produktivitas Tenaga Kerja pada Perusahaan Dodol Jaya Rasa Kecamatan Cilawu Kabupaten Garut - Rohimat Nurhasan (Fakultas Ekonomi Universitas Garut, 2016)
The purpose of this study is to analyze the effect of causal compensation on labor productivity. The data used are primary data and secondary data, using a questionnaire. The population of this study were all employees of the Company Dodol Jaya Rasa, Ilawu District, Garut Regency. The number of samples studied was 90 employees. The analytical tool used in this study is a test of validity, reliability and simple linear regression. The results of this study indicate that compensation simultaneously affects labor productivity.